1974
DOI: 10.1172/jci107880
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Corticosteroids on Human Monocyte Function

Abstract: A B S T R A C T This report examined the effect of corticosteroids in vitro on human peripheral blood monocytes, essential cells in both immune and nonimmune cellular defense mechanisms. Monocyte chemotaxis in response to sera, Escherichia coli filtrate, and lymphokine chemotactic factor was markedly reduced (P < 0.01) by hydrocortisone succinate (HCS) at 16 Ag/ml. Methylprednisolone succinate and unesterified hydrocortisone produced similar impairment of monocyte chemotaxis while two drugs which unmodified do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
75
0
2

Year Published

1975
1975
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 242 publications
(87 citation statements)
references
References 31 publications
(22 reference statements)
10
75
0
2
Order By: Relevance
“…The downregulation of the cell-mediated immune response by corticosteroids has been previously reported (14,15) and therefore the additional corticosteroid treatment during severe M. pneumoniae pneumonia may have a favorable effect by reducing the hyperimmunemediated pulmonary injury. In addition, corticosteroids downregulate the immune responses mediated by Th1 cells, and therefore corticosteroids may reduce the immunemediated pulmonary injury induced by M. pneumoniae.…”
Section: Discussionmentioning
confidence: 83%
“…The downregulation of the cell-mediated immune response by corticosteroids has been previously reported (14,15) and therefore the additional corticosteroid treatment during severe M. pneumoniae pneumonia may have a favorable effect by reducing the hyperimmunemediated pulmonary injury. In addition, corticosteroids downregulate the immune responses mediated by Th1 cells, and therefore corticosteroids may reduce the immunemediated pulmonary injury induced by M. pneumoniae.…”
Section: Discussionmentioning
confidence: 83%
“…In the latter study Atkinson et al demonstrated that IgG-sensitized erythrocytes were cleared in corticosteroid-treated guinea pigs as if they had fewer IgG molecules per red cell, suggesting a decreased recognition of immunoglobulin-or complement-coated cells by the macrophages of the reticuloendothelial system of the steroid-treated animal. Indeed recent studies have shown that corticosteroids can affect macrophage (9) and monocyte (10) activity. However, none of these studies have shown an effect of corticosteroids on monocyte or macrophage receptor function.…”
mentioning
confidence: 99%
“…GCs have been reported to interfere with a variety of both intra-and extracellular activities of mononuclear phagocytes, and GC receptors have been identified in monocytes and macrophages [725] . Hydrocortisone and prednisone diminished human monocyte chemotaxis [726] , bactericidal capacity [727,728] , receptor activity for IgG and C3 complement [727] , and specifically inhibited macrophage elastase, collagenase, and PAI secretion [729] . Moreover, GCs inhibited the expression and action of most cytokines [730] .…”
Section: Atherosclerosismentioning
confidence: 99%